Chem E Car Programme to develop student’s creativity - Nadira Hana, Abdul Hamid (2018)
Nearly 60 primary school students from year four, five and six from Sekolah Kebangsaan Bunut Rendang, Kuantan participated in Chem E Car Programme organized by Faculty of Electrical & Electronics Engineering, UMP, held on November 22, 2018.